Fantasia lusitana - Canijo, João 1957-; Schygulla, Hanna 1943-; Vogler, Rüdiger 1942-; Patey, Christian ca. 20. Jh (Midas Filmes, 2010)
"Images and sounds expose the duality of Portugal during the days of WW2: a peaceful, god-loving, rural country, providing an escape route for over one hundred thousand European refugees to the Americas; and a political and cultural elite that disguised their Nazi inclinations just enough to play its neutral role in international politics." [amazon.co.uk]
Original: Portugal 2010
Extras: a Nau Portugal ; exposição de flores na Tapada da Ajuda ; entrevista João Canijo ; entrevista Irene Flunser Pimentel (historiadora) ; entrevista Fernando Rosas (historiador) ; filmografia João Canijo
Bildformat 4:3
Keywords: Zweiter Weltkrieg; Salazarismus; Portugal; Film; DVD-Video